(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the forms, methods, and tools used to enrich the vocabulary of primary school students, as well as to develop their independent thinking and expressive speech skills. Within the framework of the new state educational standard, the teacher’s professional knowledge and methodological competence are considered essential factors. Through vocabulary-focused activities, students master literary language, activate passive vocabulary, and develop the ability to use words in accordance with language norms. Furthermore, the article explores the methodological foundations, practical forms, and scientific-research aspects of vocabulary development, presenting effective strategies used in this process.